2008
DOI: 10.1177/000348940811700804
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of Laryngeal Suspension and Upper Esophageal Sphincter Myotomy as Treatment for Life-Threatening Aspiration

Abstract: In most of our patients, life-threatening aspiration was successfully treated by UES myotomy and laryngeal suspension with restoration of oral intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…However, despite the fact that a clear volume increase can be accomplished, the lipofilling injections nevertheless did not improve function in all of our patients. Currently, it is well acknowledged that dysphagia post‐surgery and/or chemoradiotherapy is multifactorial in its physiological basis, which indicates that other factors such as fibrosis, reduced hyolaryngeal elevation, pharyngeal constrictor activity, and/or insufficient sphincter opening may also be an important factor besides volume loss . This might explain why improving just one element was not sufficient to make significant gains for some cases, though it was for others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the fact that a clear volume increase can be accomplished, the lipofilling injections nevertheless did not improve function in all of our patients. Currently, it is well acknowledged that dysphagia post‐surgery and/or chemoradiotherapy is multifactorial in its physiological basis, which indicates that other factors such as fibrosis, reduced hyolaryngeal elevation, pharyngeal constrictor activity, and/or insufficient sphincter opening may also be an important factor besides volume loss . This might explain why improving just one element was not sufficient to make significant gains for some cases, though it was for others.…”
Section: Discussionmentioning
confidence: 99%
“…Often, due to insufficient contact between the base of tongue and posterior pharyngeal wall, the food bolus is swallowed less powerfully, leading to stagnation of food (residue), with a high risk of aspiration of the residue. A combination of decreased tongue strength, deficient/reduced hyolaryngeal elevation, lack of pharyngeal constrictor activity, lack of oropharyngeal seal, or insufficient opening of the esophageal inlet may also play a role in aspiration . Long‐term and even lifelong feeding tube dependency is sometimes unavoidable, and quality of life in these patients is often seriously impaired …”
Section: Introductionmentioning
confidence: 99%
“…If the result of UES myotomy is not successful because of insufficient pharyngeal propelling combined with insufficient laryngeal elevation, additional laryngeal suspension can be considered [15]. …”
Section: Discussionmentioning
confidence: 99%
“…In our study we observed none of these complications. Dauer[15] reports one pharyngocutaneous fistula in eight patients treated with an external myotomy. Larger studies have not reported this complication[3, 7].…”
Section: Discussionmentioning
confidence: 99%
“…Profound OPD is typically a consequence of a combination of reduced lingual and pharyngeal contraction pressure and limited or absent laryngohyoid elevation . CPM alone is frequently insufficient to prevent aspiration, because the UES opening is an active mechanical event dependent on elevation of the larynx off of the cervical spine rather than simply a consequence of cricopharyngeus muscle relaxation . The laryngohyoid complex can be elevated surgically to mechanically open the UES .…”
Section: Introductionmentioning
confidence: 99%